Efficacy and safety of liposomal bupivacaine administration in the pediatric population: a scoping review of the literature - Patel, Tarika D.; Dusza, Matthew; Lee, Cheng-Ting (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Liposomal bupivacaine (LB; Exparel) is a slow-release formulation of bupivacaine used for postoperative pain control that allows for steady and sustained release of bupivacaine over an extended period of time. Although it has been thoroughly investigated in adults since initial approval in 2011, the efficacy and safety of LB use in pediatric patients have still not been fully explored since its more recent approval for pediatrics in March 2021. To assess the current state of the literature regarding the safety and efficacy of LB use in pediatric patients, we queried three online electronic databases. Overall, 26 articles encompassing 1,496 LB patients were selected for review. Outcome data on adverse events, postoperative opioid use, postoperative pain, length of hospital stay, and total hospital costs were extracted. Two published randomized controlled trials were identified, in addition to 15 retrospective cohort studies and 9 case series/case reports. The most commonly reported measures were postoperative opioid use and pain scores, followed by adverse events, length of hospital stay, and lastly, hospital costs. There were no reported instances of local anesthetic systemic toxicity, and no trends were found between surgery type or administration method (nerve block versus intramuscular injection) and surgical outcomes. While the existing literature suggests that LB may reduce pain scores, hospital costs, length of hospital stay, and opioid use, these findings are significantly limited by potential conflicts of interest, gaps in study design, and inconsistent outcome measures. Overall, there is a scarcity of high-quality studies comparing LB to more commonly used local anesthetics, and further investigation through high-quality studies, such as randomized controlled trials, is warranted to determine if LB should be included as part of a multimodal regimen for postoperative pain management in pediatric patients.